2015
DOI: 10.1002/bjs.9681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neoadjuvant chemotherapy on resectability of stage III and IV hepatoblastoma

Abstract: The majority of stage III and IV hepatoblastomas achieved radiographic resectability after two cycles of chemotherapy. There may be an opportunity for earlier surgical intervention and potential for a reduction in chemotherapy in a considerable number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
0
21
1
1
Order By: Relevance
“…PRETEXT III intermediate-risk tumors, however, should be considered for resection after the second cycle and no later than after the fourth cycle, with trisectionectomy or extreme resection often required (Figure 3). In one study of 20 patients, the majority of PRETEXT III and IV tumors achieved radiographic resectability after completion of two chemotherapy cycles [25], thus allowing for earlier resection and reduction in chemotherapy.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…PRETEXT III intermediate-risk tumors, however, should be considered for resection after the second cycle and no later than after the fourth cycle, with trisectionectomy or extreme resection often required (Figure 3). In one study of 20 patients, the majority of PRETEXT III and IV tumors achieved radiographic resectability after completion of two chemotherapy cycles [25], thus allowing for earlier resection and reduction in chemotherapy.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…There have been and are several ongoing attempts to determine which patients should proceed to OLT and after how many cycles of chemotherapy . Currently, the COG recommends evaluation for surgery after two rounds of neoadjuvant chemotherapy; however, a more recent study by Venkatramani and colleagues demonstrated that some tumors continue to regress between cycles two and four.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the COG recommends evaluation for surgery after two rounds of neoadjuvant chemotherapy; however, a more recent study by Venkatramani and colleagues demonstrated that some tumors continue to regress between cycles two and four. Giving four vs. two rounds of neoadjuvant therapy increased the percentage of tumors downstaged from 30% to 45%, but increased the percentage deemed “resectable” from 65% to 80%, leading the authors to suggest that additional chemotherapy, if tolerated, may allow for more patients to undergo successful resection . Resection avoids the possible risks of post‐transplant immunosuppression and some authors have endorsed extreme resection techniques such as extended and non‐anatomic hepatectomy to achieve negative margins .…”
Section: Discussionmentioning
confidence: 99%
“…Ancak iki kür tedavi sonrasında tümörün çok küçülmeyeceğini belirterek, daha fazla ısrar etmeden karaciğer nakli önerenler bulunmaktadır. Bu şekilde kemoterapiye bağlı işitme kaybı veya kalp yetmezliği komplikasyonlarının da azaltılabileceği vurgulanmaktadır (15) . …”
Section: Hepatoblastom Yaygınlığını Değerlendirmeunclassified